Analisis Karakteristik dan Profil Pengobatan Pasien Demam Berdarah Dengue Anak di Instalasi Rawat Inap Rumah Sakit Samarinda Medika Citra Tahun 2020-2021: Analysis of Characteristics and Medication Profile of Dengue Hemorrhagic Fever Patients in Children at the Inpatient Installation of Samarinda Medika Citra Hospital in 2020-2021 - Jessyca Azzahra; Angga Cipta Narsa; Novianty Indjar Gama (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Dengue hemorrhagic fever (DHF) is an acute viral infectious disease caused by the dengue virus. In general, DHF treatment is supportive and symptomatic. Supportive treatment is administering replacement fluids for the body, such as intravenous fluids. As symptomatic therapy, paracetamol can be given as an antipyretic. This study aimed to determine the characteristics and treatment profile of pediatric patients diagnosed with DHF at the inpatient installation of Samarinda Medika Citra Hospital in 2020-2021. The research method used is observational research which will then be described descriptively. Based on the results of the characteristics of most patients, namely in male patients (62.4%) with school-age patients (6-18 years) (80%), the degree of severity experienced by DHF pediatric patients is degree 1 of (78, 4%) with an average length of stay of 4 days (28.8%) the average weight of pediatric patients with DHF is 20-